GWAS-Identified Variants for Obesity Do Not Influence the Risk of Developing Multiple Myeloma: A Population-Based Study and Meta-Analysis - Sánchez-Maldonado, José Manuel; Cabrera-Serrano, Antonio José; Chattopadhyay, Subhayan; Campa, Daniele; Garrido, María Del Pilar; Macauda, Angelica; Ter Horst, Rob; Jerez, Andrés; Netea, Mihai G; Li, Yang; Hemminki, Kari; Canzian, Federico; et al. (International journal of molecular sciences, 2023)
Multiple myeloma (MM) is an incurable disease characterized by the presence of malignant plasma cells in the bone marrow that secrete specific monoclonal immunoglobulins into the blood. Obesity has been associated with the risk of developing solid and hematological cancers, but its role as a risk factor for MM needs to be further explored. Here, we evaluated whether 32 genome-wide association study (GWAS)-identified variants for obesity were associated with the risk of MM in 4189 German subjects from the German Multiple Myeloma Group (GMMG) cohort (2121 MM cases and 2068 controls) and 1293 Spanish subjects (206 MM cases and 1087 controls). Results were then validated through meta-analysis with data from the UKBiobank (554 MM cases and 402,714 controls) and FinnGen cohorts (914 MM cases and 248,695 controls). Finally, we evaluated the correlation of these single nucleotide polymorphisms (SNPs) with cQTL data, serum inflammatory proteins, steroid hormones, and absolute numbers of blood-derived cell populations (n = 520). The meta-analysis of the four European cohorts showed no effect of obesity-related variants on the risk of developing MM. We only found a very modest association of the POC5rs2112347G and ADCY3rs11676272G alleles with MM risk that did not remain significant after correction for multiple testing (per-allele OR = 1.08, p = 0.0083 and per-allele OR = 1.06, p = 0.046). No correlation between these SNPs and functional data was found, which confirms that obesity-related variants do not influence MM risk.
Keywords: transportní proteiny; Genome-Wide Association Study; multiple myeloma; jednonukleotidový polymorfismus; genetic variants; susceptibility; Obesity; lidé; Polymorphism, Single Nucleotide; mnohočetný myelom; genetická predispozice k nemoci; Genetic Predisposition to Disease; Risk Factors; Carrier Proteins; obezita; celogenomová asociační studie; rizikové faktory; Multiple Myeloma; obesity; Humans